Influence of Different Plant Densities and Plant Growth Promoting Rhizobacteria (PGPR) on Yield and Yield Attributes of Corn (Zea maize L.) - Mir Naser Seiedi2, Vahid Ashrafi1*, (Recent Research in Science and Technology, 2010)
In order to study the effects of different plant densities andÂ seed priming with plant growthÂ promotingÂ rhizobacteria (PGPR) onÂ yield and yield attributesÂ ofÂ corn (Zea maize L.), a factorial experiment based on randomized complete block design with three replications was conducted in 2010 at the Research Farm of Islamic Azad University, Ardabili Branch. Treatments were three densities containing, 7 (D1), 9 (D2) and 11 plant m-2(D3) plus seed priming with Plant Growth Promoting Rhizobacteria (PGPR) in three levels containing, without inoculation (as control), priming with Azotobacter chroococcum strain 5 and Azosprilium lipoferum strain OF. Maize hybrid was SC-404. Results indicated that plant density had significant effects on grain yield, plant height, number of kernels per ear, the number of grain rows and number of grains per ear row. These characteristics had different response to seed priming with PGPR. The highest grain yield obtained from D2. The highest the number of kernel per ear and the number of grain per ear row recorded at D1, while D3 showed the highest values of plant height. The number of grain row did not affected by levels of plant density and seed priming with PGPR. In conclusion, it can be suggested that in order to increase of grain yieldÂ should be applied 9 plants m-2 in seed priming withÂ Azosprilium lipoferum strain OF inÂ conditions ofÂ ArdabilÂ Plain.